Аналіз напрямків сталого управління та селективного збору відходів споживання - Титаренко, А. І.; Соболєв, С. А.; Шестопалов, Олексій Валерійович (ФОП Яроченко Я. В., 2024)
Conceptual government bases by the system of handling the offcuts of consumption in the context of steady development are analysed. For diminishing of amount of offcuts of consumption the system of selective separate collection of offcuts of consumption is described with the purpose of their subsequent processing and offered separate collection of offcuts of housing and unhousing to the sector.
Keywords: відходи; утилізація відходів; сміття; селективний збір; стале споживання; сортування сміття